The significance of HLA typing in transplantation - Shirin Farjadian (Society of Diabetic Nephropathy Prevention, 2012)
Although genetic admixture has recently occurred among different ethnic groups with the increased rates of migration to big cities, information about HLA allele distribution in different ethnic groups in Iran may still be helpful to improve the selection of transplantation donor candidates from certain ethnic groups which are genetically closer to the recipient. Because the data reported by Einollahi et al. reflect a large HLA disparity among Iranian kidney recipients, any improvement could play a small yet important role in organ transplantation.